Effect of "freedom of choice" on Task Performance and Well-Being During Leisure Activity: An Intercultural Study Among Older Adults in China and France. (September 2022) - Tang, Minmin; Wang, Dahua; Guerrien, Alain
Based on the perspective of self-determination theory (SDT) and the cross-cultural, the aim of the present study was to explore the effect of "freedom of choice" on the well-being of institution-dwelling older adults (elderly residences and nursing homes), in particular during leisure activities. Participants ( N China  = 67, M age  = 80.55 years; N France  = 90, M age  = 82.19 years) were randomly assigned to the "elderly-choice" group or "staff choice" group to participate in a puzzle game. Consistent with SDT, results showed that basic psychological needs satisfaction (autonomy, competence, relatedness) was positively associated with elderly well-being. However, our findings did not demonstrate the importance of freedom of choice for promoting such well-being in the context of leisure activities for either culture; this may be related to the recompense of close relationships or else the particularity of the elderly population. Interestingly, competence satisfaction was observed to act as a complete mediating variable between task performance and well-being only in the French population.